Partai Politik Lokal di Daerah Otonomi Khusus: Perbandingan Yuridis Aceh dan Papua - Musrafiyan Musrafiyan; Mutiara Fahmi; Zahlul Pasha Karim (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
The existence of local political parties is one of the special powers for Aceh and Papua Provinces. Unlike Aceh, the rules regarding local political parties in Papua are not clearly stated in Law no. 21 of 2001 concerning Special Autonomy for Papua Province. This paper attempts to analyze the comparison between Law Number 11 of 2006 concerning the Government of Aceh and Law Number 21 of 2001 on Special Autonomy for the Province of Papua regarding local political parties, and the consequences for Aceh and Papua of differences in local political party arrangements. The method that the author uses is library research with a law approach and a sociological approach. The results of the research show that the Aceh special autonomy law contains 20 articles concerning the formation of local political parties. Furthermore, the existence of local political parties in Aceh can be seen in the participation of some of these parties in the 2009 2014 and 2019 general elections. While Article 28 of the Papua Special Autonomy Law which accommodates political parties does not have permanent legal force to be further interpreted as local political parties. it is also not applicable because it is not equipped with government regulations regarding the formation of local political parties in Papua. Even the Constitutional Court through its decision Number 41/PUU-XVII/2019 rejected the judicial review of Article 28 of the Papua Special Autonomy Law.